Selected Topics in Almost Periodicity - Kostić, Marko, 1977- (De Gruyter studies in mathematics, 2022)
Covers uniformly recurrent solutions and c-almost periodic solutions of abstract Volterra integro-differential equations as well as various generalizations of almost periodic functions in Lebesgue spaces with variable coefficients. Treats multi-dimensional almost periodic type functions and their generalizations in adequate detail.